2001
DOI: 10.1007/pl00000232
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P-selectin specific cell adhesion by a low molecular weight, non-carbohydrate compound, KF38789

Abstract: A novel low molecular weight compound, KF38789, specifically inhibited P-selectin-dependent cell adhesion and the leukocyte recruitment in mouse peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…E, F). To further validate the role of P‐selectin, embryos were treated with KF38789, a selective inhibitor of P‐selectin‐mediated cell adhesion ; CD41:eGFP + cell counts showed that KF38789 also caused reduced CHT colonization, particularly in AM1241‐treated embryos (Fig. G, H).…”
Section: Resultsmentioning
confidence: 99%
“…E, F). To further validate the role of P‐selectin, embryos were treated with KF38789, a selective inhibitor of P‐selectin‐mediated cell adhesion ; CD41:eGFP + cell counts showed that KF38789 also caused reduced CHT colonization, particularly in AM1241‐treated embryos (Fig. G, H).…”
Section: Resultsmentioning
confidence: 99%
“…B). Three well‐known tubulin disruptors (vincristine, vinblastine and colchicine), one tubulin stabilizer (Taxol) and KF 38789, which was originally identified as a selective inhibitor of P‐selectin‐mediated cell adhesion and recently identified as a tubulin disruptor , were classified into the same cluster. These results suggested that the calculated parameters and cluster analysis work well and reflect the features of cellular status.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified selectins as potential targets for the design of novel antiinflammatory agents, including selectin antagonists (19-22, 24, 34-42) and selectin-targeted immunoliposomes designed for local delivery of compounds to the endothelium (43)(44)(45)(46). Research has focused on identifying the structural features required for high selectin binding affinity, and based on these studies, some low molecular weight, noncarbohydrate, nonpeptide inhibitors of P-selectin have been identified (34)(35)(36)(37)40). Therapeutically viable P-selectin inhibitors have proven difficult to realize due to the weak binding of the monovalent ligands and extreme cost associated with the production of physiological ligand-based inhibitors such as sLe x or PSGL-1.…”
Section: Discussionmentioning
confidence: 99%